Exploring Cohesions in EFL Academic Writing: A State of the Art on the Study of Cohesions - Uru, Orvi Banja; Sudirman, Anselmus; Nugroho, Andhi Dwi (Elsya : Journal of English Language Studies, 2021)
Cohesion has become a crucial component of academic writing that promotes the semantic connection within phrases and sentences. The objectives of this literature review research are to identify different forms of cohesions and the most common form of cohesion in articles on EFL academic writing. This study extracted records from Google Scholar and Scopus databases and selected 20 studies in the last five years out of 700 on the use of cohesions in the writing of EFL students. The data was gathered by sorting similar messages, finding cohesions, clarifying cohesions, and counting the cohesions with the highest percentage. The research results show that the published articles containing cohesions represent the reference (35%), paired conjunctions (15%), reiteration (40%), and collocation (10%). The most common type of cohesion is reiteration, which is essential for comprehending what the authors mean in their published works. Cohesions in theoretical and practical grounds contribute to the explicitness of semantic components of words or phrases to generate the messages conveyed to readers.